2020
DOI: 10.1002/dvdy.163
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in the developing retina couple phagocytosis with the progression of apoptosis via P2RY12 signaling

Abstract: Background: Microglia colonize the developing vertebrate central nervous system coincident with the detection of developmental apoptosis. Our understanding of apoptosis in intact tissue in relation to microglial clearance of dying cells is largely based on fixed samples, which is limiting given that microglia are highly motile and mobile phagocytes. Here, we used a system of microglial depletion and in vivo real-time imaging in zebrafish to directly address microglial phagocytosis of apoptotic cells during nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 82 publications
(144 reference statements)
9
51
1
Order By: Relevance
“…2e), which is again in line with the finding that upon PLCγ2 KO in iMGs, the expression of P2RY12 is strongly diminished [6]. Although P2ry12 is a well-established homeostatic microglia marker [31], it has been considered also as a specific marker for healthy rodent CNS microglial cells [32] and is known to mediate microglia motility, phagocytosis of apoptotic cells, and protection of the bloodbrain-barrier [33][34][35]. Also, the expression pattern analysis of P2RY12 in response to β-amyloid in aging human brain has suggested that P2RY12 expression by microglia should not be considered solely as a marker of resting microglia [36].…”
Section: Resultssupporting
confidence: 81%
“…2e), which is again in line with the finding that upon PLCγ2 KO in iMGs, the expression of P2RY12 is strongly diminished [6]. Although P2ry12 is a well-established homeostatic microglia marker [31], it has been considered also as a specific marker for healthy rodent CNS microglial cells [32] and is known to mediate microglia motility, phagocytosis of apoptotic cells, and protection of the bloodbrain-barrier [33][34][35]. Also, the expression pattern analysis of P2RY12 in response to β-amyloid in aging human brain has suggested that P2RY12 expression by microglia should not be considered solely as a marker of resting microglia [36].…”
Section: Resultssupporting
confidence: 81%
“…Additionally, the extensive cell turnover through apoptosis during brain development is again an important step for creating homeostasis and generating a functional brain. For that to be accomplished, cellular apoptosis drives microglial colonization and establishment in the CNS for a coordinated and efficient system of clearance/removal of apoptotic bodies by microglia, whereas inefficient phagocytosis of apoptotic bodies results, instead, in subsequent cell death alongside with inflammatory and immune responses because of the released intracellular contents [ 73 , 74 ]. Microglia are essential to remove apoptotic neural progenitor cells within the neurogenic niches of the hippocampus-subgranular and subventricular zones-via activation of TAM receptor tyrosine kinases MerTK and AXL [ 75 ], but also mediated by the complement system, as the C1q complement protein was recently found expressed on microglial phagocytic pouches during hippocampal neurogenesis [ 76 ].…”
Section: Microglial Phagocytosismentioning
confidence: 99%
“…Microglia are essential to remove apoptotic neural progenitor cells within the neurogenic niches of the hippocampus-subgranular and subventricular zones-via activation of TAM receptor tyrosine kinases MerTK and AXL [ 75 ], but also mediated by the complement system, as the C1q complement protein was recently found expressed on microglial phagocytic pouches during hippocampal neurogenesis [ 76 ]. Apart from the hippocampus, microglia also phagocytosed apoptotic Purkinje neurons, for the proper maturation of rat cerebellum and correct development of the retina in zebrafish, a process that is surprisingly delayed after inhibition of microglial purinergic receptor P2RY12, thus unveiling an additional role of purinergic signaling in developmental phagocytosis of apoptotic cells [ 74 , 77 ]. On the other hand, current studies on microglia associate cell phagocytosis with the brain’s sexual differentiation.…”
Section: Microglial Phagocytosismentioning
confidence: 99%
“…For instance, in the embryonic development of the eye, microglia entrain proximal cytosocial stimuli (such as complement cascade proteins, local chemokine milieu, and spontaneous neural activity) in the massive culling of excess neurons during the self‐organization of the crystal‐like regularity of the retina. [ 104,105 ] Postnatally, external photic stimuli rapidly drive further microglia‐mediated activity‐dependent organization of the retina, optic tracts, and primary visual cortex. [ 106,107 ] Then, as suggested by literature cited above, as the infant interacts with the environment in visually‐guided goal‐directed behavior, salient social stimuli (e.g., recognition of maternal face and expressions) begin the microglia‐mediated process of activity‐dependent sculpting of social behavior and memory circuits (presumed to be highly evolved and complex corticolimbic and corticohypothalamic pathways) [ 108 ] that preferentially and increasingly respond to psychosocial stimuli in infancy and early childhood.…”
Section: Microglia As Evolutionarily Adaptable Agents: From Embryonicmentioning
confidence: 99%